1991
DOI: 10.1071/ar9910053
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Heterodera avenae Woll. in South Australia

Abstract: Population changes of the cereal cyst nematode (Heterodera avenae Woll.) under various rotational regimes in the field were examined. A density of 5 eggs/g soils caused a loss of about 10% in yield of wheat cv. Bayonet under the experimental conditions. Maximum multiplication rate at low initial densities was about l0x, but this rapidly decreased as initial density increased. Equilibrium levels ranged from 15 eggs/g soil up to 40 eggs/g under different conditions. The resistant wheat, Aus 10894, maintained an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…The lack of increased total hatch due to root diffusates is similar to the results obtained by Fisher and Hancock (1991), who did not find an increase of total hatch of H. avenae in root diffusates. Williams and Beane (1979) found a slight increase in hatch of H. avenae from England in response to root diffusate in experiments lasting for 35 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…The lack of increased total hatch due to root diffusates is similar to the results obtained by Fisher and Hancock (1991), who did not find an increase of total hatch of H. avenae in root diffusates. Williams and Beane (1979) found a slight increase in hatch of H. avenae from England in response to root diffusate in experiments lasting for 35 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…The reduction in grain yield increased with both increasing P i and P f . Meagher and Brown (1974), Fisher and Hancock (1991), Ibrahim et al (1999), Al-Hazmi et al (1999) and Smiley et al (2005a) reported similar results with H. avenae. In a similar experiment conducted by Fisher and Hancock (1990) a density of 5 egg (g soil) −1 or fewer of H. avenae caused a significant loss of about 10% in yield of wheat.…”
Section: Discussionsupporting
confidence: 81%
“…Storey (1982) continued the detailed seasonal investigation of the development of G. rostochiensis and found that population changes occurred initially close to the planting depth of the potato tuber, the timing and scale at the other depths being correlated with the cysts position relative to that of the planted tuber. However, in other parts of the world the influence of the nematophagous fungi were shown tobe less than in Northern Europe and the population dynamics of H. avenae considerably different (Fisher and Hancock, 1991). The monitoring, during the different seasons of the year, of the cereal cyst nematode by Lopez-Llorca (1988) has lead to a better understanding of the infection process of the nematophagous fungi which Kerry (1974; had shown could naturally keep cereal cyst nematode populations below economic threshold levels in the British Isles.…”
Section: Surveillancementioning
confidence: 95%